E-LKPD based on Problem Based Learning (PBL) Approach to Measure Mathematics Literacy Ability of Elementary Students - Mulyasari, Dini Wahyu; Gunarhadi; Roemintoyo (Universitas Pendidikan Ganesha, 2022)
Students in Indonesia are still experiencing problems related to the low level of mathematical literacy in Indonesia. PBL-based E-LKPD reflection seeks to develop students' mathematical literacy skills. The purpose of this study is to analyses need for learning resources, namely E-LKPD based on Problem Based Learning (PBL) in an effort to improve students' mathematical literacy skills. The research method used is descriptive quantitative method. The participants in this study consisted of 13 fifth grade elementary school students, followed by two (2) teachers. Data collection techniques in the study used mathematical literacy questionnaires, observations and interviews. Meanwhile, the results will be analyzed using interactive analysis techniques consisting of data reduction, presenting data and presenting conclusions. The results showed that teachers tend to be resistant to technology, where teachers still use conventional and non-problem-based worksheets. So, the results of the initial test show that students' mathematical literacy is quite low. Can be concluded that through PBL-based E-LKPD will be proper as a learning resource, the teacher hopes that students will become more accustomed and familiar in solving daily problem-based problems and this is one of the drivers of increasing students' mathematical literacy skills.